From Transanal Total Mesorectal Excision to Transanal Transection with Single-Stapled: Evolution of Transanal Techniques - Crippa, Jacopo; Foppa, Caterina; Spinelli, Antonino (Digestive Disease Interventions, 2023)
The last decades have seen a remarkable improvement in colorectal surgery, as new techniques and protocols have been developed and adopted. Restoring the continuity of the intestinal tract after low rectal surgery remains one unresolved challenge. The development of new transanal techniques to approach the lowest rectum paved the way for a switch in mentality. Transanal total mesorectal excision has seen a steep adoption by colorectal surgeons, combining the transanal pathway with the use of minimally invasive techniques to overcome the historical difficulties of the anterior approach. One step ahead in the evolution of the transanal approach could be represented by the recently described transanal transection with single stapled technique, developed to address the main concerns of previous transanal approaches thus providing oncological and functional balance.
Keywords: rectal surgery; transanal surgery; rectal cancer; anastomotic techniques; TaTME; TTSS